Sobre calificación escolar - Fernández Huerta, José (Revista Española de Pedagogía, 2019)
One of the problems that has frequently appeared in this century is that of the qualification of the school children, a problem that has been resolved in different ways according to the basic hypothesis on which they were founded. If they are founded on the polyfactorial theory the only admissible solution will consist in independently resolving each specification of children's culture, but if they are founded on the substantial unity of the human being we shall be obliged to resolve them by summing up all the aspects of the school life in only one appreciation. In this article it is tried to show one of the several sistems which may exists to verify the hylomorphical doctrine. Before amply treating the problems and solutions which are connected to the attendance, behaviour and learning there is that of the complete union in only one note. A statistical study of the results in a complete course of study allows the author to attain conclusions enough to justify this study.
Keywords: calificación escolar; Revista Española de Pedagogía